(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2018)
Water scarcity is a very critical issue in the context of sustainability and global environmental change. However, the notion of scarcity also has its local roots that are constructed by diverse actors with specific values, knowledge and interests. This paper explores the socially constructed nature of water scarcity among diverse social actors along the river basin of Bharathapuzha in Kerala. It also examines the diverse contextual factors that have affected the traditional land and water management practices in the river basin. This paper is based on qualitative research carried out among two villages along the river basin. The findings of this paper show that the river basin is extremely prone to drought-like situations and multiple forms of water scarcity surfaces in the discourses and discursive practices of social actors associated with the socio-ecological system. Further, these discursive practices are guided by the instrumental rationality of technological modernisation and progress, which has not only disrupted the traditional water management systems in the region, but also have completely neglected the ecosystem linkages and carrying capacities of vulnerable resource systems. The state-induced and expert-driven images of modernity such as dams, concrete check dams and major irrigation projects have replaced the traditional imagery of the river as a vibrant and ever-flowing life source. Water scarcity and other related forms of scarcity mediate these transitions. These processes have long-term implications on the sustainability of the river itself.